2017
DOI: 10.14710/jitaa.42.4.255-262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of white kabesak (Acacia leucophloea Roxb) leaves level in the diet on feed intake and body weight gain of Kacang goat

Abstract: ABSTRAKTujuan penelitian ini adalah untuk menganalisis pengaruh tingkat penggunaan daun kabesak putih (Acacia leucophloea Roxb.) Willd. dalam pakan terhadap konsumsi, kecernaan pakan dan pertambahan bobot badan kambing Kacang. Rancangan Acak Kelompok dengan 5 perlakuan dan 5 ulangan digunakan dalam penelitian ini. Perlakuan tersebut berupa 5 pakan konsentrat yang masing-masing mengandung 0, 10, 20, 30, dan 40% daun kabesak putih berdasarkan bahan kering (BK) secara berturutturut sebagai perlakuan T 0 , T 1 , T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
1
1
Order By: Relevance
“…The dry matter (DM) digestibility values ranged from 84.28-88.27% and organic matter (OM) digestibility ranged from 84.57±5.12%-88.79±3.60% indicated that the use of complete silage contributed positively in fattening the male Kacang goats. The DM digestibility value in this study is higher than the results of a research conducted by Lawa et al (2017) which obtained DM digestibility values ranging from 69.3±7.76 -75.7±4.89% in the male Kacang goats given different levels of white kabesak in their feed. The variation of digestibility value in the goats is influenced by the type of feed, nutrients content of feed, as well as body weight.…”
Section: Nutrients Digestibilitycontrasting
confidence: 87%
“…The dry matter (DM) digestibility values ranged from 84.28-88.27% and organic matter (OM) digestibility ranged from 84.57±5.12%-88.79±3.60% indicated that the use of complete silage contributed positively in fattening the male Kacang goats. The DM digestibility value in this study is higher than the results of a research conducted by Lawa et al (2017) which obtained DM digestibility values ranging from 69.3±7.76 -75.7±4.89% in the male Kacang goats given different levels of white kabesak in their feed. The variation of digestibility value in the goats is influenced by the type of feed, nutrients content of feed, as well as body weight.…”
Section: Nutrients Digestibilitycontrasting
confidence: 87%
“…The results of dry matter degradation in each treatment gave different values caused by the high and low crude fibre and crude protein content in each treatment. According to Wijayanti [14], CF content affects the degradation value because feed containing high CF content reducing feed digestibility.…”
Section: Proximate Profilementioning
confidence: 99%
“…Peranan ternak kambing yang penting ini perlu didukung melalui penyediaan lingkungan yang sesuai bagi pertumbuhan kambing, seperti dikemukakan Coffey et al (2004) (Wina dan Syahgiar, 1991). Daun kabesak putih yang merupakan tanaman lokal endemik di pulau Timor mengandung PK 14,7%, SK 30,4% dan LK 0,07% (Lawa, et al, 2017 (Kushartono dan Iriani, 2004). Leguminosa sebagai pakan ternak mempunyai susunan zat makanan yang sangat baik, selain itu daunnya sangat disukai ternak kambing.…”
Section: Pendahuluanunclassified